Superior photocatalytic behaviour of novel 1D nanobraid and nanoporous α-Fe2O3 structures - Sundaramurthy, Jayaraman (2013)
We have produced novel nanostructures of pure and ceramic α-Fe2O3 using electrospinning, followed by annealing at 500 °C for 5 h with ramp rate of 5 °C min−1. Electron microscopy clearly reveals the novel morphologies, namely nanobraids and nanoporous α-Fe2O3, suggesting that the precursor, (iron(III) acetylacetonate, (Fe(acac)3)) to polyvinylpyrrolidone (PVP) ratio greatly influences structural transformations of Fe2O3. 4 wt% of Fe(acac)3/PVP solution used for electrospinning at 15 kV a potential produced nanobraid-like ceramic α-Fe2O3, indicating that binodal phase separation is predominant at this ratio. On the other hand, the electrospinning of 6 wt% of Fe(acac)3/PVP solution induces spinodal phase separation that results in the formation of nanoporous ceramic α-Fe2O3 fibers. The nanobraids and nanoporous ceramic α-Fe2O3 exhibit superior photocatalytic performances of up to 91.2% and 90.2% for the organic dye, Congo red (CR) in the shorter time of 140 min under photoirradiation. It is concluded that the presence of the porous surface and smaller crystallite size in the α-Fe2O3 nanostructures act as active catalytic centers and play a key role in allowing effective interaction between organic dye and α-Fe2O3, in turn enhance photocatalytic degradation performance.